6*(x+1)=2*(5+3x)

Simple and best practice solution for 6*(x+1)=2*(5+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6*(x+1)=2*(5+3x) equation:


Simplifying
6(x + 1) = 2(5 + 3x)

Reorder the terms:
6(1 + x) = 2(5 + 3x)
(1 * 6 + x * 6) = 2(5 + 3x)
(6 + 6x) = 2(5 + 3x)
6 + 6x = (5 * 2 + 3x * 2)
6 + 6x = (10 + 6x)

Add '-6x' to each side of the equation.
6 + 6x + -6x = 10 + 6x + -6x

Combine like terms: 6x + -6x = 0
6 + 0 = 10 + 6x + -6x
6 = 10 + 6x + -6x

Combine like terms: 6x + -6x = 0
6 = 10 + 0
6 = 10

Solving
6 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9z+2-4=4+4z-6 | | 5(x+3)=10-2(x+2) | | 2(120-5x/10) | | -30-6n=-10-2(3n+10) | | 1.2=0.1x | | 3x+2(x-2)+9=0 | | x-(.3x)=28 | | (.3x)-x=28 | | 10-k=k-6 | | 0.41x+x=117 | | 3*(x+1)=2*(x+11) | | x^2-13x-23=-4x-1 | | .3x-x=28 | | -3(-5v-4v-4y+3)= | | (4x^(2/7))(3x^(1/3)) | | 9*(z-3)=12z | | 5x-105=-4x+30 | | -3x-7+2x+5x-11x= | | 5x-x-7=-4x+2 | | (3x+1)+4i=-2+(3y-2)i | | 0.5x^2-3x+4=0 | | 10x+64+5x=65x-36 | | -3-2(6)= | | -2(x+6)+3x= | | 3x-10=5x+45 | | 6y=10x-4 | | 3x+2y=73 | | 5x-6+6x-8=x+4+x+10 | | x^2+8=-8x+1 | | 10x-7y=11 | | 600t^2+60t-3=0 | | 140=x^(1/2) |

Equations solver categories